Carbon Fibers - Jonathan Phillips (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Remarkably, truly novel structures are still being found for materials made of a single element: carbon. Perhaps there is a 'revolution' in carbon-only materials. Indeed, recently, two Nobel prizes were awarded for new forms of carbon: for fullerenes in 1996, and for graphene in 2010. And the magic and beauty of carbon nanotubes has held the attention of the scientific world for more than a decade. Yet, there is still more to discover and to explain. In this Special Issue, the focus is on just one area of carbon research: fibers. Even given this relatively narrow focus there is a diversity of research that is both compelling and frustrating. Compelling as it demonstrates the vitality of the subject, and frustrating as it makes it difficult to organize. The topics covered include new fiber fabrication protocols, the mechanical behavior of fiber reinforced polymers, new techniques to study the microstructure of fiber containing composites, new uses of fiber structures, the use of carbon fibers as catalyst supports, and studies regarding the difficulties of machining fiber structures for inclusion in complex structures.